52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0213
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Vortex Interference Associated with Missile Configurations

Abstract: Studies of vortex-induced aerodynamic nonlinearities associated with body and fin vortices for missile configurations have been performed. As part of this effort, the vortex and fin modeling methodologies in the engineering-level and intermediate-level aerodynamic predictions codes MISL3 and MISDL have been reviewed and improved. The ability of the methods to predict detailed fin loads in the presence of external vortices is demonstrated. Both codes have been used extensively to predict missile performance inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…These methods are primarily based on NASA wind tunnel data and have been developed into engineering-level and intermediate-level aerodynamic prediction codes [7][8][9]. The models have also been extended to include canard interaction [10,11] but the experimental work is restricted to wind tunnels, so only considers steady state responses to fixed canard angles. Therefore, these methods are primarily for designing responsive canards in missiles and have not been used to understand actual rocket flight, where there are very fast movements and transient effects that often behave very differently to steady state response in a wind tunnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are primarily based on NASA wind tunnel data and have been developed into engineering-level and intermediate-level aerodynamic prediction codes [7][8][9]. The models have also been extended to include canard interaction [10,11] but the experimental work is restricted to wind tunnels, so only considers steady state responses to fixed canard angles. Therefore, these methods are primarily for designing responsive canards in missiles and have not been used to understand actual rocket flight, where there are very fast movements and transient effects that often behave very differently to steady state response in a wind tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…This paper develops models of rocket roll dynamics that are first identified in the wind tunnel at low speeds and then validated on actual rocket launches at much higher speeds. This type of validation is unique in the literature as most other approaches do not go any further than wind tunnel evaluation [10,11]. The UC rocketry modelling and control methodology is to use a combination of dynamic subsonic wind tunnel testing and sounding rocket launches, to test qualitatively methodologies that have the ability to account for new dynamics in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the VFI effects are critical to the performance of the munition because the downwash of the canard vortices can reduce the effectiveness of the tail fins with potentially detrimental effects [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The interactions depend strongly on how the canards are deflected (i.e., for roll, pitch, or yaw control) and the angles of attack under consideration.…”
mentioning
confidence: 99%
“…Much of this research on the VFI has been conducted on the NASA Blair missile configuration at supersonic speeds [9,10] for a slender body (large length-to-diameter ratio) with canards and tail fins aligned in roll orientation. The results of the Blair wind-tunnel studies have been used to improve engineering-level and intermediate-level aerodynamic prediction codes [15][16][17], which use panel methods, vortex-cloud methods, or other semi-empirical methods to account for the vortices shed from the canards and body. The aerodynamic prediction codes give reasonable results over the parameters for which they have been validated and can model the flow interaction effects for a supersonic missile.…”
mentioning
confidence: 99%
“…1,2,[5][6][7][8] The application and benefit of these tools are widespread including a more efficient design and testing process. As aircraft performance increases, missile capabilities must also advance to continue to be effective.…”
mentioning
confidence: 99%